Monitoring equity in immunization coverage - Enrique Delamonica; Alberto Minujin; Jama Gulaid (The World Health Organization, 2005)
This paper analyses trends in coverage of three doses of diphtheria-pertussis-tetanus vaccine (DPT3) by wealth groups in selected countries. It discusses the depth of disparities in coverage by wealth and changes during the 1990s. Complete assessment of equity in income and its trends have been discussed in other papers, however issues related to children's well-being have often been brushed aside because the comparable data needed to fully understand and rectify inequalities is lacking. A focal point of this paper pertains to gathering any and all information recorded about the immunization of children and then transcribing these data so that it is applicable to all countries. We analyse the technical difficulties and methodological solutions that would enable comparisons to be made between various measures of inequity taken from different surveys at two or three points in time among a variety of subpopulations in order to obtain disaggregated data. This paper argues for a simultaneous analysis of changes in averages and disparities in immunization coverage along variables of interest, such as wealth, gender and place of residence in order to achieve a better understanding of trends. We also focus on measurement issues and describe trends in immunization by wealth. We conclude with a brief discussion of issues related to monitoring equitable outcomes and offer suggestions for further research. In addition, the paper presents some lessons that can be drawn about monitoring and policies. We hope that this analysis of patterns of disparities will help policy-makers in devising, proposing and executing efficient policies and interventions.